Psychometric properties of the Burmese version of Self-Stigma Scale: A study among older Myanmar migrants in Thailand - Shun Lei Oo; Moe Moe Yu; Wongpakaran, Tinakon; Griffiths, Jiranan; Lerttrakarnnon, Peerasak; O’Donnell, Ronald R.; Wongpakaran, Nahathai (Narra J, 2026)
Self-stigma is a major barrier to mental health help-seeking among marginalized populations, including older Myanmar migrants in Thailand. Despite its importance, this issue has been little studied in this population, and no validated Burmese-language instrument has been available to date. This study evaluated the psychometric properties of the Burmese version of the Self-Stigma Scale–Short Form (SSS-SF), with particular emphasis on its factor structure, reliability, and validity among older Myanmar migrants in Thailand. Participants (n=211) aged ≥60 years were recruited through online platforms and community outreach initiatives. The SSS-SF was translated and culturally adapted in accordance with international guidelines. Confirmatory factor analysis was used to test multiple structural models, and reliability was assessed using Cronbach’s alpha. Convergent and discriminant validity were examined through correlations with the depression and anxiety subscales of the Outcome Inventory-21 (OI-21), the Mental Help-Seeking Intention Scale (MHSIS), and the Extraversion domain of the Zuckerman-Kuhlman-Aluja Personality Questionnaire-20 (ZKA-20). Initial analyses indicated that the 9-item bifactor model provided the best representation of the data, although overall fit remained only modest. After removal of four misfitting items, a shortened 5-item version demonstrated improved fit as a unidimensional model. Reliability was good for the 9-item scale (α=0.855) and acceptable for the 5-item scale (α=0.828). Convergent validity was supported by significant positive correlations between self-stigma and OI-21 depression (r=0.55, p<0.01), OI-21 anxiety (r=0.54, p<0.01), and MHSIS (r=0.15, p<0.05). Discriminant validity was supported by a weak, non-significant association with ZKA-20 Extraversion (r=0.11, ns). These findings suggest that, although the original 9-item Burmese SSS-SF showed limitations in model fit, the refined 5-item version offers a more concise measure with initial evidence of promising psychometric properties for assessing self-stigma among older Myanmar migrants. This shorter version may be useful for rapid screening in community and clinical settings, although further validation in other Burmese populations is warranted.